Zingiber mekongense Gagnep. (Zingiberaceae): A new Distribution Record for the Flora of Vietnam - Huong, Le Thi; Huong, Trinh Thi; Huong, Nguyen Thi Thanh; Sam, Ly Ngoc (VNU Journal of Science: Natural Sciences and Technology; Vol 36 No 2, 2020)
Zingiber mekongense  Gagnep., which found in the Central Vietnam, is here reported as a new record for the flora of Vietnam. Voucher specimens collected in the Binh Thuan, Nghe An and Thanh Hoa provinces and deposited in the major herbaria: the herbarium of the Biology (Vinh University), HN, VNM. A detailed morphological description and a coloured photographs of this species along with data on distribution, ecology, phenology and notes to its allies are given.